1984
DOI: 10.1007/bf00263150
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous copolymerization behavior of styrene and ethyl methacrylate at high conversion

Abstract: SUMMARYStyrene and ethylmethacrylate were copolymerized in bulk at 62~and several monomer feed ratios. At moderately high conversion, anomalous copolymerization behaviour occurred. Although the onset of the departures from expected copolymerization behaviour seems to be related to the onset of the gel-effect, this relation did not hold when mimicking higher conversion by adding an amount of homopolymer.Obviously the propagation reactions are not only affected by changes in diffusion characteristics but also by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The continuous lines in Figure represent the average molar fractions calculated by the Skeist equation knowing the initial molar fraction of the BODPY monomer and using the reactivity ratios tabulated for the corresponding model monomers, i.e., styrene (S) for πS 5 , phenyl methacrylate (PhMA) for πPhMA 1 etc. ). ,− In all cases the plots matched well the experimental data points. It can thus be concluded that the tabulated reactivity ratios for model monomers are valid to estimate the microstructure in the fluorescent copolymer.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The continuous lines in Figure represent the average molar fractions calculated by the Skeist equation knowing the initial molar fraction of the BODPY monomer and using the reactivity ratios tabulated for the corresponding model monomers, i.e., styrene (S) for πS 5 , phenyl methacrylate (PhMA) for πPhMA 1 etc. ). ,− In all cases the plots matched well the experimental data points. It can thus be concluded that the tabulated reactivity ratios for model monomers are valid to estimate the microstructure in the fluorescent copolymer.…”
Section: Resultssupporting
confidence: 71%
“…styrene (S) for πS 5, phenyl methacrylate (PhMA) for πPhMA 1 etc.). 18,31,32,33 In all cases the plots matched well the experimental data points. It can thus be concluded that the tabulated reactivity ratios for model monomers are valid to estimate the microstructure in the fluorescent copolymer.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation